2016
DOI: 10.1002/pc.24067
|View full text |Cite
|
Sign up to set email alerts
|

Impedance spectroscopy study of polyester/carbon nanotube composites

Abstract: The electrical properties of carbon nanotubes loaded in polyester polymer matrix were studied by using the impedance spectroscopy technique. The study was carried out in the frequency range between 100 Hz and 1 MHz and temperature between 170 and 400 K. Cole–Cole representation was used to interpret the impedance spectra of all the samples. The variation of the electrical conductivity, as a function of temperature, for concentrations higher than the conduction threshold was analyzed. This variation undergoes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
3
8
0
Order By: Relevance
“…The Nyquist plot of EIS results shows only one semicircle, which we attribute to the tunneling conductivity of materials. The tunneling current ceases to dominate at these voltage values, [ 38 ] and electrical breakdowns between separated CB particles and aggregates occur. Therefore, for the application of the composite, where high conductivity is required, a voltage higher than ≈2 V should be used to prevent the impact of nonlinear tunneling current.…”
Section: Resultsmentioning
confidence: 99%
“…The Nyquist plot of EIS results shows only one semicircle, which we attribute to the tunneling conductivity of materials. The tunneling current ceases to dominate at these voltage values, [ 38 ] and electrical breakdowns between separated CB particles and aggregates occur. Therefore, for the application of the composite, where high conductivity is required, a voltage higher than ≈2 V should be used to prevent the impact of nonlinear tunneling current.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, great efforts have been dedicated to fabricating wearable electronic textiles using carbon nanotubes, carbon nanofibers, graphene‐based materials, or hybrids of them. Among them, some studies on wearable electronic textiles fabricated by traditional textiles like cotton, nylon‐6, polyester, and silk fabrics coated with graphene oxide (GO) by using bovine serum albumin (BSA) as glue have been reported. Yun et al reported a new e‐textile produced by RGO/nylon‐6 textiles by using BSA as a glue.…”
Section: Introductionmentioning
confidence: 99%
“…The tested microcoil was found to exhibit a strong frequency‐dependent AC resistance, which is believed to be due to the non‐ohmic resistances associated with polymer composite films at frequencies below <10 MHz. [ 31,35 ] Similar frequency‐dependent impedances have been observed in polymer composites with carbon‐based conductive filler components. [ 36–38 ] Comparing the fabricated microcoil's impedance behavior to these previously studied polymer composite films suggests that at the 1 wt% rGO particle loading, the electrical performance is driven mainly by the material properties instead of geometry.…”
Section: Figurementioning
confidence: 59%
“…In addition to being a useful method of characterizing the electrical performance of composite materials, [ 31 ] impedance spectroscopy is a common technique used in microfluidic devices with integrated microelectronics designed for biological analysis such as cell or bacterial detection, [ 32 ] particle detection, [ 33 ] and chemical sensing. [ 34 ] To investigate the AC performance of the microstructures fabricated with the developed photocomposite, an 8‐turn microcoil printed between two patterned ITO contact pads was printed (Movie S3, Supporting Information), with an rGO particle loading of 1 wt%.…”
Section: Figurementioning
confidence: 99%